2009
DOI: 10.1137/080734352
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Total Fenchel Duality for Convex Optimization Problems in Locally Convex Spaces

Abstract: Abstract. We consider the optimization problem (P A ) inf x∈X {f (x) + g(Ax)} where f and g are proper convex functions defined on locally convex Hausdorff topological vector spaces X and Y , respectively, and A is a linear operator from X to Y . By using the properties of the epigraph of the conjugated functions, some sufficient and necessary conditions for the strong Fenchel duality and the strong converse Fenchel duality of (P A ) are provided. Sufficient and necessary conditions for the stable Fenchel dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Motivated by recent results on stable strong and total duality for constrained convex optimization problems in [2,6,7,9,13,17] and the ones on zero duality gap in [15,16] we introduce in this paper several regularity conditions which characterize ε-duality gap statements (with ε ≥ 0) for a constrained optimization problem and its Lagrange and FenchelLagrange dual problems, respectively. The regularity conditions we provide in Section 2 are based on epigraphs, while the ones in Section 3 on ε-subdifferentials.…”
Section: Preliminariesmentioning
confidence: 99%
“…Motivated by recent results on stable strong and total duality for constrained convex optimization problems in [2,6,7,9,13,17] and the ones on zero duality gap in [15,16] we introduce in this paper several regularity conditions which characterize ε-duality gap statements (with ε ≥ 0) for a constrained optimization problem and its Lagrange and FenchelLagrange dual problems, respectively. The regularity conditions we provide in Section 2 are based on epigraphs, while the ones in Section 3 on ε-subdifferentials.…”
Section: Preliminariesmentioning
confidence: 99%
“…Our characterization is motivated by [11], where in the classical setting, strong Fenchel duality is equivalent to the inequality (f + A ) (0) (f A ) (0) ; together with the exactness of the infimal convolution at the point 0; being f and A proper and convex functions. In [6] it was shown that, if v (P ) 2 R and f + A = sup n a j a 2 e E f; A o ; condition (C3) is sufficient for strong Fenchel duality.…”
Section: Proposition 41 Condition (C F ) Guarantees Stable Strong Fementioning
confidence: 99%
“…In the convex setting with finite dimensional space, background information on Fenchel duality is due to Rockafellar [26,27]. With infinite dimensional space, we refer for instance to [5,7,11,23,17].…”
Section: Proof (I) ⇒ (Iimentioning
confidence: 99%